B21 Characterisation Of Mice Overexpressing Mutant Huntingtin Lacking The Spine Morphogenesis Regulator Kalirin-7. (17th September 2014) - Magg, JCD; Portal, E; Clemens, LE; Weber, JJ; Fehrenbacher, B; Schaller, M; Söhn, A; Mains, R; Riess, O; Nguyen, HP
Abstract : Background: Kalirin-7, a postsynaptic density protein which interacts with the huntingtin-associated-protein-1, has several common interactors with huntingtin as PSD95 and NMDAR2B. Kalirin-7 is important for the generation and maintenance of synaptic dendrites and glutamatergic synapses. Glutamatergic N-methyl-D-aspartate receptor (NMDAR)-mediated excitotoxicity has been implicated in Huntington's disease (HD) pathophysiology for a long time. But the mechanisms mediating NMDAR toxicity in HD are still not clear. Aim: In this study, we investigated the effect of kalirin-7 deficiency in a HD mouse model Methods: Kalirin-7 knockout (Kal7KO) mice were crossbred with a transgenic huntington mouse model (YAC128) carrying a YAC construct with the fulllength human huntingtin with 128CAG repeats. Male mice underwent a behavioural characterisation including activity, motor learning, cognition and anxiety testing. Protein biochemistry and histology were used to assess effects of kalirin-7-deficiency on huntingtin aggregation, glutamate receptor subunit levels and synapse morphology in cortex and striatum. Results: Kalirin-7 deficiency does not affect the motor performance of YAC128 mice on the rotarod nor does it influence activity in an automated home cage system. Interestingly, Kalirin-7 deficiency reduces anxiety of YAC128 on the elevated plus maze. Spatial learning, memory or relearning in YAC128 mice in a simple swimming test are not modulated by the lack of Kalirin-7. On protein level, Kalirin-7 deficiency leads to the upregulation of larger Kalirin isoforms in YAC128 mice whereas levels of NMDAR subunits are not affected. The aggregate load of YAC128 mice is not changed by lack of kalirin-7. Moreover, the absence of Kalirin-7 does not change nor cause a difference in synapse morphology of YAC128 mice. Conclusions: Kalirin-7 deficiency specifically influences the anxiety phenotype of YAC128 mice but does not affect aggregate load or NMDAR toxicity linked parameters.